Essence of Harmony - Stojanović, Lidija (Poznańskie Studia Slawistyczne, 2022)
The paper aims to explore the harmonious relations between man and nature, in terms of ecopsychology, representing a solutionfor pointless/deviant discussions in the field of post- and transhumanism, especially in the abnormal period of the pandemic. According to the author, the establishment of harmony is primarily contained in the “moderation” of the senses and the ratio through intuitive knowledge. The establishment of several patterns of harmony will be considered through Honeyland ( 2019 ), the poetry of Koneski, and the eco analysis of Miljovska. The paper will examine the intuitive human abilityto establish this harmony, seen as a process of creating cosmic balance. The analyzed works manifest the harmonious relationship: human—biotope, principles of “eco-cosmos” of the local man.